Antibodies to the N-Terminal Block 2 of Plasmodium falciparum Merozoite Surface Protein 1 Are Associated with Protection against Clinical Malaria - Cavanagh, David R. (American Society for Microbiology, 2004)
This longitudinal prospective study shows that antibodies to the N-terminal block 2 region of the Plasmodium falciparum merozoite surface protein 1 (MSP-1) are associated with protection against clinical malaria in an area of stable but seasonal malaria transmission of Ghana. Antibodies to the block 2 region of MSP-1 were measured in a cohort of 280 children before the beginning of the major malaria transmission season. The cohort was then actively monitored for malaria, clinically and parasitologically, over a period of 17 months. Evidence is presented for an association between antibody responses to block 2 and a significantly reduced risk of subsequent clinical malaria. Furthermore, statistical survival analysis provides new information on the duration of the effect over time. The results support a conclusion that the block 2 region of MSP-1 is a target of protective immunity against P. falciparum and, thus, a promising new candidate for the development of a malaria vaccine.